User Interface Design and User Experience Proto-Type Mobile-Based Interior Design Service Application (Case Study: Kirana Mebel Interior) - Dewi, Wiwiek Nurkomala; Rahadian, Kevin Surya; Sulhan, Muhammad Afif; Suwandi, Suwandi (Proceeding International Conference on Religion, Science and Education, 2025)
Kirana Mebel Interior is a growing company engaged in furniture and furniture. Kirana Mebel Interior is a growing group of young companies with passion and creative ideas, working together to create great masterpieces. Kirana Mebel Interior wants to take advantage of technological advances to support and advance the Kirana Mebel Interior company itself. By creating an application that can support promotions and make it easier for Kirana Mebel Interior to reach buyers that cannot be done manually or door to door. As a media promotion and to enliven the buyers of Kirana Mebel Interior, the designer plans to make a User Interface Design And User Experience (UI/UX ) Design Prototype Application that provides Services for Interior Design available in one application and display, which is hoped to be developed into an application in the future. The data analysis method that will be used by the designer is the use of User Persona, User Flow, Wire flow, and Design System. For the design using Wireframe from each page. While the software used is Figma. After being adjusted to the analysis at Kirana Mebel Interior, it is hoped that the Application Prototype can be useful as the basis for making the application.